PERAN MEDIA SOSIAL SUARA.COM DALAM MENJAGA EKSISTENSINYA SEBAGAI MEDIA BERITA - Krisnawati, Ester; Frisca Ivena Archie (MEDIALOG: Jurnal Ilmu Komunikasi, 2024)
The rapid development of technology and the internet today makes all community activities connected to social media. From what used to be people getting information through radio, television, and newspapers, now every individual can get the latest information through social media alone, such as Instagram, Facebook, TikTok, Website, and other media. With the existence of social media, every news media is competing to attract its reading audience. One of them is Suara.com news media, how does the media maintain its existence as a news media so that its audience continues to read and get news from Suara.com. This research uses a qualitative approach method by conducting interviews, data collection, and observation on Suara.com's social media accounts. The results of this study are Maintaining the existence and audience awareness of Suara.com, there is a need for consistency in making news and content. Making news that is packaged attractively and building interactive relationships with audiences can build the image of Suara.com news media in social media.